The Influence of Application of The Number Head Together Learning Model Based on Edutainment Responsibility Learning Application (EDURESPECT) on Problem Solving Ability of Elementary Students - Wanabuliandari, Savitri; Ardianti, Sekar Dwi; Sari, Lia Permata; Tanghal, Analiza B.; Yahya, Faridah Hanim (Asian Journal of Applied Education (AJAE), 2023)
This study has the objectives of (1) solving the average difference in students' problem-solving abilities, (2) testing the increase in students' problem-solving abilities. This research is included in the pre-experimental quantitative research with the one group pretest posttest design. The data in this study were analyzed using the paired sample t test which aims to test the average difference, and the n-gain score test to test the increase. The research was conducted in class V SD 5 Bae. From this study, the results obtained were (1) there were differences in students' problem-solving skills before and after the NHT model was applied with edutainment responsibility learning application media, (2) there was an increase in students' problem-solving abilities with a percentage of 52.66%.